Administrative Settlement of Real Estate Numbering Disputes In Algerian Legislation - عجابي صبرينة (Milev Journal of Research and Studies, 2023)
Despite the existence of a comprehensive legal framework aimed at regulating the real estate registration process in Algeria, practical implementation has revealed numerous complex issues, resulting in many individuals being denied their rightful property, particularly in relation to property numbering. Consequently, an increasing number of disputes have been brought before the judiciary in this area. The objective of this study is to identify the most significant problems related to property numbering and propose administrative solutions to address them before resorting to a judicial settlement. The ultimate goal is to ensure the purification of real estate ownership and the organization of the real estate sector in both Algerian legislations. It is worth noting that reconciliation constitutes the primary administrative procedure conducted by the real estate registrar to prevent real estate disputes and reach an amicable settlement that satisfies all parties involved.